2006
DOI: 10.1051/0004-6361:20053812
|View full text |Cite
|
Sign up to set email alerts
|

MACHOs in M 31? Absence of evidence but not evidence of absence

Abstract: We present results of a microlensing survey toward the Andromeda Galaxy (M 31) carried out during four observing seasons at the Isaac Newton Telescope (INT). This survey is part of the larger microlensing survey toward M 31 performed by the Microlensing Exploration of the Galaxy and Andromeda (MEGA) collaboration. Using a fully automated search algorithm, we identify 14 candidate microlensing events, three of which are reported here for the first time. Observations obtained at the Mayall telescope are combined… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 45 publications
2
80
1
Order By: Relevance
“…Indeed, to get a more meaningful comparison for the selflensing contribution, we normalised the values for the mass of the luminous components to those of the MEGA models. We found that our estimate of the (total) number of the self-lensing events agrees with the [18] prediction only when considering more extreme (maximal) parameters for the disk component.…”
Section: Pos(gmc8)043mentioning
confidence: 46%
See 4 more Smart Citations
“…Indeed, to get a more meaningful comparison for the selflensing contribution, we normalised the values for the mass of the luminous components to those of the MEGA models. We found that our estimate of the (total) number of the self-lensing events agrees with the [18] prediction only when considering more extreme (maximal) parameters for the disk component.…”
Section: Pos(gmc8)043mentioning
confidence: 46%
“…1). In contrast, the MEGA collaboration [18] finds that their results, although not conclusive, agree with a no MA-CHO hypothesis. Although the issues involved in the microlensing observations towards the LMC or the M31 are indeed rather different, the results for the halo fraction in the form of MACHOs depend crucially on the prediction of the expected signal due to known luminous populations, this being dominated by the "self-lensing" signal where both source and lens belong to the same star population residing respectively either in the LMC or in M31.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations